55.4k views
1 vote
Use factoring and the zero-product property to find the zeros of:
f(x) = 2x² + 3x-2

Use factoring and the zero-product property to find the zeros of: f(x) = 2x² + 3x-example-1

1 Answer

7 votes
First, set the equation to 0.

0 = 2x^2 + 3x - 2

From there, you want to find two numbers that equal the product of a (2) and c (-2) that add up to b (3)

The two numbers would be 4 + -1 = 3

Then, put these in the equation:

2X^2 + 4X - X -2

From here, you can factor into two groups.

2X(x + 2) -1(x +2)

Your factors would be (2X - 1)(X + 2).

The zeroes would be 1/2 and -2 when setting each part to zero.

2X - 1 = 0; x = 1/2
X+2 = 0; x = -2



User Zaynab
by
6.3k points